2007
DOI: 10.1007/s00280-007-0573-x
|View full text |Cite
|
Sign up to set email alerts
|

Third-line therapy for metastatic colorectal cancer

Abstract: Third-line therapy in advanced colorectal cancer may improve mOS for patients with MCRC. Therefore, randomized studies should be conducted in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…For example, the objective response rate (ORR) for third-line treatment in lung cancer was only ~6–23% (6). The ORRs for the most common chemotherapy regimens used in third-line therapy for metastatic colorectal cancer vary from 5 to 36% (7).…”
Section: Intractable Cancermentioning
confidence: 99%
“…For example, the objective response rate (ORR) for third-line treatment in lung cancer was only ~6–23% (6). The ORRs for the most common chemotherapy regimens used in third-line therapy for metastatic colorectal cancer vary from 5 to 36% (7).…”
Section: Intractable Cancermentioning
confidence: 99%
“…One could argue that it was the change in chemo regime rather than the surgical resection that helped the patient. In a recent review paper [ 10 ], Gundgaard et al reported median time to progression (mTTP) up to 7 months and a medium overall survival (mOS) of 16 months with third line chemotherapy. The highest mÔÔP, 9.8 months, was reported for the combination of cetuximab combined with irinotecan, the treatment our patient received.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that a solitary adrenal metastasis should be resected immediately to achieve good prognosis in some cancer types [14][15]. According to the histopathological diagnosis, chemoregimen might be changed [14].…”
Section: Discussionmentioning
confidence: 99%
“…In autopsy studies, the prevalence of incidentaloma is 1-9% [13] and the rate of metastasis ranges from 1.9-17.4% [1,9]. It is generally accepted that a solitary adrenal metastasis should be resected immediately to achieve good prognosis in some cancer types [14][15]. According to the histopathological diagnosis, chemoregimen might be changed [14].…”
Section: Discussionmentioning
confidence: 99%